La inteligencia emocional como competencia estratégica de los líderes en la gestión con teletrabajadores (2021)
At present, successful organizations and leaders in their sectors are those that have human capital with high standards in competencies and skills, but also with elements in their collaborators that are not common and that make a difference, this characteristic is what makes them different and allow them to achieve objectives in a successful way, these collaborators are those called leaders, who in addition to their training, skills and expertise have the management of emotional intelligence as an element and competitive advantage over others. The new work scenarios challenge us and invite us to evolve and generate new practices, one of many is Telework, a work modality that requires leaders with emotional intelligence management as a basic tool for remote interaction with work teams, thus generating motivation, positive attitudes, orientation to the achievement of objectives and above all commitment and loyalty towards the company and personal development. To conclude, our present forces us every day to develop and grow as individuals, to discover ourselves and have the ability to adapt to different situations that require us to show our leadership and management of emotional intelligence with ourselves and our work teams. The research consists of an introduction, objectives, statement of the problem, justification, antecedents, delimitation and a section with the theoretical review on emotional intelligence, leadership and telework. The methodology is analyzed to continue with the development of the specific objectives and finalize with the conclusions, recommendations and bibliography used.